Integrated Quality Management as the Focus of Attention and Target of Teaching Supervision at SDTQ-T Irsyadul Aulad - Zahrah, Zahrah; Ansari, Adi (Journal of Educational Research and Practice, 2024)
This research was conducted at SDTQ-T Irsyadul Aulad School, South Basirih, East Banjarmasin Sub-district, Banjarmasin City. The focus of this study was to explore the practical implications and effectiveness of IQM implementation in improving the quality of education at the school. This research discusses how the implementation of IQM can influence the quality of learning, improve teacher performance and facilitate the participation of school members in the process of continuous improvement of education quality. Data were collected through literature review, interviews and documentation. Interviews were conducted with 2 informants, namely the supervisor and teachers in the school. The data collected were then analyzed qualitatively, the qualitative method was chosen because this article aims to understand and describe the teaching supervision program at SDTQ-T Irsyadul Aulad. The data analysis technique used in this research is thematic analysis[B1]. Thematic analysis is conducted by identifying, categorizing, and interpreting data obtained from literature study, interviews, and documentation. This research explores the concept of teaching supervision in the context of Integrated Quality Management (IQM) at SDTQ-T Irsyadul Aulad. The main findings show that teaching supervision is a continuous coaching process to improve the quality of learning. Teaching supervision at SDTQ-T Irsyadul Aulad can improve the quality of learning, help teachers achieve goals, and develop teachers' professionalism. Teaching supervision can be measured through several specific indicators, such as increasing the frequency of classroom observations by principals and supervisors, using structured constructive feedback for teachers after observations, conducting periodic training sessions and workshops focusing on innovative teaching strategies, and increasing teachers' participation in professional discussion forums. This research proves that IQM is an effective supervision model to improve the quality of education, with tangible results seen at SDTQ-T Irsyadul Aulad Banjarmasin. It can provide practical implications for other schools that want to implement a similar approach.